A Class of Variable-Order Fractional p·-Kirchhoff-Type Systems. (27th February 2021) - Wu, Yong; Qiao, Zhenhua; Hamdani, Mohamed Karim; Kou, Bingyu; Yang, Libo
Abstract : This paper is concerned with an elliptic system of Kirchhoff type, driven by the variable-order fractional p x -operator. With the help of the direct variational method and Ekeland variational principle, we show the existence of a weak solution. This is our first attempt to study this kind of system, in the case of variable-order fractional variable exponents. Our main theorem extends in several directions previous results.